PENINGKATAN KETERAMPILAN BERBICARA MENGGUNAKAN METODE SOSIODRAMA KELAS VI SEKOLAH DASAR - Ariani Herlita; Siti Halidjah; Tahmid Sabri (Universitas Tanjungpura, 2020)
AbstractThe purpose of this study was to improve students' speaking skills using the sociodrama method in class VI SDN 54 West Pontianak. The method used is descriptive. The form of research used is classroom action research (CAR). This research is collaborative in nature. The research activities were carried out in class VI of 54 Pontianak Barat Elementary School with 36 subjects in class VI. The results of the study showed that the speaking ability of students on the base line contained 61.11% (22 people) who were incomplete and only 43.75% (14 people) who had completed an average value of 70.53. In the implementation of the first cycle there was an increase in the process of speaking skills of students using the sociodrama method there were 52.77% (19 students) which were complete while 47.22% (17 students) were incomplete with an average value of 72.44. In the implementation of the second cycle the improvement experienced by students in the process of speaking skills using the sociodrama method experienced an increase of 81.11% (31 students) which was complete while those that were incomplete was 13.88% (5 students), while the average value was 82.38 and in cycle III the improvement experienced by students in the process of speaking skills using the sociodrama method was 94.44% (34 students) which was complete while those that were incomplete was 5.55% (2 students) with an average value of 88.19 It can be concluded that by using the Sociodrama method can improve the speaking skills of students in grade VI 54 Pontianak Elementary School. Keywords : Improvement, Speaking Skills, Indonesian Language Learning, Sociodrama Method.